Experimental and Computational Analysis of UHMWPE-Based Multi-Layered Bulletproof Vests Under 9mm Projectiles Impact - Timotius, Hizkia; Sastranegara, Azhari; Hernawan, Rendi; Sutisna, Nanang Ali; Anggraini, Lydia (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
This study investigates the ballistic performance and energy absorption of multi-layered UHMWPE bulletproof vests against 9mm projectiles using experiments and finite element simulations (LS-DYNA). Two configurations were analyzed: a conventional structure and a sandwich-layered design incorporating UHMWPE, titanium (Ti6Al4V), and PVC. Ballistic tests, conducted per NIJ Level IIIA standards, were validated through simulations. The sandwich-layered vest exhibited superior energy dissipation, achieving BFS values of 12.03 mm (experiment) and 12.36 mm (simulation), effectively reducing blunt trauma risk. The multi-material approach enhanced penetration resistance and impact force distribution, while numerical models closely matched experimental findings, confirming reliability. Results demonstrate the feasibility of lightweight, high-performance ballistic armor. Future work will explore material optimization, configuration refinements, and testing with higher-caliber projectiles for broader applications.